Geochemistry of Carboniferous coals from the Laoyaogou mine, Ningwu coalfield, Shanxi Province, northern China: Emphasis on the enrichment of valuable elements. (1st November 2020) - Liu, Bangjun; Wang, Junyan; He, Hongtao; Mishra, Vivek; Li, Yanheng; Wang, Jinxi; Zhao, Cunliang
Highlights: Geochemistry of coal in the Laoyaogou Mine from Shanxi Province have been studied. The No. 5 Coal is enriched with several valuable elements, especially Li, Zr and Hf. Most of the enriched elements have inorganic affinities, except for Sr and REY. Valuable elements, especially Li, are enriched in Ningwu coalfield and Qinshui Basin. The coals from Shanxi Province have a potential value with these valuable elements. Abstract: This paper provides new geochemical data focussing on valuable elements and their origins in the coals from the Laoyaogou mine, Ningwu coalfield, Shanxi Province, northern China. Kaolinite, pyrite, calcite, and boehmite are the main minerals, along with a small amount of illite and anatase, present in the coals studied. The studied coals are enriched with Li, Ga, Zr, Zn, Hf, Sr, Nb, Sn, Th, and REY, especially the case of high average concentration of Li (163.42 μg/g) which is more than ten-times higher than that in world hard coals. Zirconium and Hf, the average concentrations of which are more than five-times higher than those in world hard coals. Lithium, Ga, Zr, Hf, and Th have strong inorganic affinities, whereas Sr and REY have organic affinities. The main carrier of Li in the No. 5 Coal is kaolinite, illite, and boehmite. Gallium, Zr, Hf, and Th probably have the same origin and are largely associated with kaolinite and Ti/Ca-bearing minerals which originate from the source region. In Shanxi Province, the main coalfields are enriched in several valuable elements (e.g. Li, Ga, Zr, Hf, and Th), especially the high average content of Li in the Ningwu coalfield (116 μg/g) and the Qinshui Basin (110 μg/g). The Laoyaogou coals and the coals from the main coalfields in Shanxi Province have economic significance as hidden treasures of the coals themselves and in their by-products.